2016
DOI: 10.1038/gene.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of KIR3DL1/KIR3DS1 polymorphism in Behçet’s disease

Abstract: The Behçet’s disease (BD)-associated HLA allele, HLA-B*51 (B*51), encodes a ligand for a pair of allelic killer immunoglobulin-like receptors (KIR) present on cytotoxic cells — KIR3DL1, which inhibits their cytotoxicity, and KIR3DS1, which activates their cytotoxic activity. We tested whether KIR-regulated mechanisms contribute to BD by testing for association of KIR3DL1/KIR3DS1 genotypes with disease in 1799 BD patients and 1710 healthy controls from Turkey, as well as in different subsets of individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…The distribution of KIR3DL1 and 3DS1 in BD was evaluated in a large cohort of Turkish. Similarly to our results, no association was found in the whole cohort neither in subgroups with B51, Bw4, or Bw4-80I (16) but this study did not investigate variants on this gene. Variants in KIR3DL1 have been reported as associated with the disease in two high throughput studies (10, 17), although none of them was designed to investigate the possible involvement of functional variants in this disease.…”
Section: Discussionsupporting
confidence: 84%
“…The distribution of KIR3DL1 and 3DS1 in BD was evaluated in a large cohort of Turkish. Similarly to our results, no association was found in the whole cohort neither in subgroups with B51, Bw4, or Bw4-80I (16) but this study did not investigate variants on this gene. Variants in KIR3DL1 have been reported as associated with the disease in two high throughput studies (10, 17), although none of them was designed to investigate the possible involvement of functional variants in this disease.…”
Section: Discussionsupporting
confidence: 84%
“…HLA-B*51 remained associated with BD in both groups (MC group; P =0.0009, OR 4.14, 95% CI 2.72–6.32, ophthalmic group; P =0.0367, OR 1.75, 95% CI 1.05–2.92) and there was no difference between the groups with regard to KIR3DL1/S1 presence/absence (data not shown). We were unable to replicate the association between an increase in KIR3DS1 alleles and ophthalmic involvement as was previously reported (26).…”
Section: Resultscontrasting
confidence: 76%
“…examined Turkish patients with BD for the presence/absence of KIR3DL1/S1 , but found no association after controlling for the effects of HLA-B*51 (25). Erer et al studied a large, carefully compiled dataset of 1799 Turkish BD patients and reported an association between KIR3DS1 and ocular disease, but no effect of KIR3DL1/S1 overall on disease-risk (26). More recently, Mohammed-Ebrahim et al examined 397 Iranian patients with BD, but found no specific KIR gene to be associated with BD (27).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluated the presence of KIR3DL1 or KIR3DS1 alleles in Turkish BD patients bearing HLA-B with a Bw4 motif. However, there no significant differences in the presence between BD patients and controls (55). Further functional studies are needed to clarify whether or not an abnormality in the balance of these two receptors has functional consequence in BD.…”
Section: Pathogenesis Of Bd From Genetic and Environmental Aspectsmentioning
confidence: 92%
“…NK cells may attack such “ HLA-B*51 low -MICA high ” mucocutaneous cells via NK receptor NKG2F. In addition, the NK receptors killer immunoglobulin-like receptor (KIR) KIR3DL1, which inhibits the NK function, and KIR3DS1, which activates the NK function, recognize HLA-B*51 Bw4 motif (55). A recent study evaluated the presence of KIR3DL1 or KIR3DS1 alleles in Turkish BD patients bearing HLA-B with a Bw4 motif.…”
Section: Pathogenesis Of Bd From Genetic and Environmental Aspectsmentioning
confidence: 99%